Paraneseuthia Franz in the Indian Himalayan Region and Western Palaearctic Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Paraneseuthia loebli sp. n. (northern India) and P. meybohmi sp. n. (central-southern Turkey) are described. This is the first record of Paraneseuthia west of Sundaland, with the Turkish species occurring over seven thousand kilometers westward from the hitherto known westernmost range of this genus. Moreover, for the first time Paraneseuthia is reported to occur in the Mediterranean zone of moderate climate. Previously proposed phylogeographic hypotheses concerning the evolution of Paraneseuthia are discussed and the currently known distribution of this genus is summarized.